Development of a qPCR Tool for Detection, Quantification, and Molecular Characterization of Infectious Laryngotracheitis Virus Variants in Chile from 2019 to 2023 - Tomás Gatica; Sebastián Salgado; Humberto Reyes; Carlos Loncoman (Animals)
Infectious laryngotracheitis virus (ILT) is the pathogen responsible for a respiratory ailment that has resulted in significant economic losses in the poultry industry, primarily due to high morbidity and mortality rates, as well as diminished egg production. However, for small producers living near the coast, where backyard flocks are located in rural areas, respiratory illness may pose a public health risk rather than an economic one, which must be considered in the differential diagnosis of ILT. Therefore, in this research, we focused on developing an efficient tool to detect, quantify, and classify infectious laryngotracheitis virus (ILTV) field variants. Our results demonstrates that qPCR detected positive samples collected between 2019 and 2023 in flocks exhibiting clinical signs of respiratory illness in Valdivia, in the Los Ríos Region of Southern Chile. Furthermore, the molecular characterization of positive samples using dideoxynucleotide sequencing revealed that the detected viruses were similar to tissue culture origin (TCO) vaccines, even though the birds had never been vaccinated. To the best of our knowledge, this is the first report characterizing ILTV variants in Chile using a molecular approach. Our findings indicate that the tool is useful for detecting ILTV and can also be used to quantify viral particles using a standard curve, making it a valuable tool for the differential diagnosis of respiratory pathogens in poultry.